The effect of IFRS adoption on earnings management and the moderating role of corporate governance: evidence from Bangladesh - Hasan, Mohammad Tariq (2020)
International Financial Reporting Standards (IFRS) is introduced with the intention to offer better financial reporting quality. The extent literature suggests that the level of earnings management (EM) is one of the determinants of financial reporting quality. However, previous studies documented inconclusive findings about the effect of IFRS adoption on EM. Few studies suggest that the extent of EM practices may not decline even after IFRS adoption, due to political, cultural, educational level or weak governance inside the organization. Thus, this study investigates the relationship between IFRS adoption and EM i.e. discretionary accruals and real earnings management (REM) in developing economy like Bangladesh. Moreover, the study also examines the relationship between corporate governance (CG) strength and EM as well as the moderating role of CG strength on the relationship between IFRS adoption and EM. Two underpinning theories, namely agency theory and contractual hypotheses of positive accounting theory were employed to explain the relationship among variables. Based on earlier literature a CG-index (CGI) was developed to measure CG strength which is followed by random effect GLS with robust regression in a balanced panel data. The study employed 94 firms for 6 years, that is 564 firm year's observation, over two time period as pre (2004-06) and post (2013-15) adoption of IFRS. The results show that IFRS and CGI both have a significant negative relationship with EM. Moreover, it is recognized that the CG strength significantly moderates the relationship between IFRS and REM. It implies that the presence of good CG may help to attain the objectives of IFRS adoption. Thus, the findings of this study will help regulators and policy-makers to understand the current accounting and corporate governance practice by firms which induce them to make CG compliance report mandatory and punitive action for non-compliance in Bangladesh.